Single vs. reimplant programs for finishing steers - Jack G. Riley; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 1984)
Finishing yearling beef steers were used to compare various implant programs in a 167-day trial. All implant programs increased daily gain ranging from 6.6 to 25.4% over non-implanted controls and improved feed efficiency ranging from .5 to 13.9%. Steers implanted with Ralgro® initially and reimplanted 75 days later with Synovex-S gained the fastest and most
Keywords: Cattlemen' s Day; 1984; Kansas Agricultural Experiment Station contribution; no. 84-300-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 448; Beef; Implant; Gain